Mercury contamination of sympatric seabirds and associated health risks in an Antarctic ecosystem - Mills, William F. (2025)
Antarctic marine ecosystems are located far from industrial pollution sources, yet mercury (Hg) contamination remains an important threat to regional biodiversity. Seabirds occupy mid- to high trophic positions in Antarctic food webs, and can show high levels of Hg contamination due to biomagnification. Here, total Hg (THg) concentrations and stable isotopes of carbon (δ13C) and nitrogen (δ15N) were measured in red blood cells of brown skuas Stercorarius antarcticus lonnbergi (n = 44) and south polar skuas S. maccormicki (n = 50) at King George Island/Isla 25 de Mayo (South Shetland Islands) in the 2022/23 and 2023/24 breeding seasons. The objectiveswere to: (i) determine current levels of Hg contamination at King George Island and identify the underlying drivers (e.g., species, sex, year, δ13C and δ15N); (ii) compare contaminant levels with other breeding sites; and (iii) examine potential Hg-associated health risks. At King George Island, south polar skuas had higher THg concentrations (mean ± SD, 3.85 ± 2.99 μg g 1 dw) than brown skuas (1.67 ± 1.25 μg g 1 dw), potentially due to their greater reliance on mesopelagic fish and carry-over effects from their non-breeding distributions. THg concentrations of males were higher than females, with deposition into eggs by females being the likeliest explanatory factor, and were positively related to δ15N, reflecting the biomagnification process. THg concentrations of brown skuas in this study were higher than at Hope Bay (Antarctic Peninsula), but lower than at SouthOrkney Islands (Antarctica), South Georgia and Kerguelen Islands (subantarctic). THg concentrations of the south polar skuas analysed here were higher than at Hope Bay and Ad´elie Land (Antarctic continent). Comparisons with toxicity benchmarks suggest that skuas are currently at low risk of Hg-associated health impacts at King George Island.